Maternal Serum Preconception Polychlorinated Biphenyl Concentrations and Infant Birth Weight - Murphy, Laurel E. (National Institute of Environmental Health Sciences, 2010)
BACKGROUND: Prenatal and postnatal polychlorinated biphenyl (PCBs) exposure has been associated with decrements in fetal and infant growth and development, although exposures during the preconception window have not been examined despite recent evidence suggesting that this window may correspond with the highest serum concentrations. OBJECTIVES: We assessed maternal serum PCB concentrations at two sensitive developmental windows in relation to birth weight. METHODS: Serum samples were collected from 99 women as they began trying to become pregnant (preconception) and after a positive pregnancy test (prenatal); 52 (53%) women gave birth and represent the study cohort. Using daily diaries, women recorded sexual intercourse, menstruation, and home pregnancy test results until pregnant or up to 12 menstrual cycles with intercourse during the estimated fertile window. With gas chromatography with electron capture, 76 PCB congeners were quantified (nanograms per gram serum) and subsequently categorized by purported biologic activity. Serum PCBs were log-transformed and entered both as continuous and categorized exposures along with birth weight (grams) and covariates [smoking (yes/no), height (inches), and infant sex (male/female)] into linear regression. RESULTS: A substantial reduction in birth weight (grams) was observed for women in the highest versus the lowest tertile of preconception antiestrogenic PCB concentration (β = −429.3 g, p = 0.038) even after adjusting for covariates (β = −470.8, p = 0.04). CONCLUSIONS: These data reflect the potential developmental toxicity of antiestrogenic PCBs, particularly during the sensitive preconception critical window among women with environmentally relevant chemical exposures, and underscore the importance of PCB congener–specific investigation.